2023
DOI: 10.1021/acs.est.3c00353
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Performance Evaluation of Reinforcement Learning Algorithms Applied to Wastewater Treatment Control Optimization

Abstract: Treatment of wastewater using activated sludge relies on several complex, nonlinear processes. While activated sludge systems can provide high levels of treatment, including nutrient removal, operating these systems is often challenging and energy intensive. Significant research investment has been made in recent years into improving control optimization of such systems, through both domain knowledge and, more recently, machine learning. This study leverages a novel interface between a common process modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It is limited to not only the PWTP but also the general wastewater treatment operations since the dynamic optimization of the real-world application involves multiple objectives and constraints in common, and the dynamic optimization environment requires strictly high flexibility, efficiency, and robustness of the optimization system. The multiagent DRL takes into account all the features above that, also as supported by the related studies, , can contribute to the treatment process to achieve the synergistic effect of pollution elimination and carbon reduction.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is limited to not only the PWTP but also the general wastewater treatment operations since the dynamic optimization of the real-world application involves multiple objectives and constraints in common, and the dynamic optimization environment requires strictly high flexibility, efficiency, and robustness of the optimization system. The multiagent DRL takes into account all the features above that, also as supported by the related studies, , can contribute to the treatment process to achieve the synergistic effect of pollution elimination and carbon reduction.…”
Section: Resultsmentioning
confidence: 97%
“…Mohammadi et al used DRL to adapt to the process’s complex dynamics, optimized the WWTP for phosphorus removal control, and suggested a comparative investigation of different DRLs in an imperfect environment. Croll et al have evaluated four common DRL algorithms systematically to minimize treatment energy in wastewater treatment control . Several review papers indicated that the links of DRL study to minimize carbon emission and balance the conflicting objectives of WWTP performances are imperative and could be promising future directions …”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been made to improve the control and operation of WWTPs toward low-carbon and sustainable. , It has been proven that implementing a proper operational control scheme may be effective for reducing GHG emissions in the WWTP . An improved cascade control structure could reduce the N 2 O emissions by nearly 30% with compromised cost and satisfied water quality .…”
Section: Introductionmentioning
confidence: 99%